2009
DOI: 10.1016/j.febslet.2009.05.033
|View full text |Cite
|
Sign up to set email alerts
|

A nucleolar protein RRS1 contributes to chromosome congression

Abstract: a b s t r a c tWe report here the functional analysis of human Regulator of Ribosome Synthesis 1 (RRS1) protein during mitosis. We demonstrate that RRS1 localizes in the nucleolus during interphase and is distributed at the chromosome periphery during mitosis. RNA interference experiments revealed that RRS1-depleted cells show abnormalities in chromosome alignment and spindle organization, which result in mitotic delay. RRS1 knockdown also perturbs the centromeric localization of Shugoshin 1 and results in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…Both Rrs1 and Ebp2 have recently been connected to a role in the progression of mitosis as well. Mybbp1a is phosphorylated by the mitotic kinase Aurora B, and it has been revealed that depletion of Mybbp1a or Rrs1 leads to a mitotic delay and abnormalities in spindle organization (45,68). Additionally, the involvement of Mybbp1a, rpL5, and rpL11 was shown in p53 acetylation and accumulation, which is dependent on the release of Mybbp1a from nucleolar RNA upon stress (54).…”
Section: Discussionmentioning
confidence: 99%
“…Both Rrs1 and Ebp2 have recently been connected to a role in the progression of mitosis as well. Mybbp1a is phosphorylated by the mitotic kinase Aurora B, and it has been revealed that depletion of Mybbp1a or Rrs1 leads to a mitotic delay and abnormalities in spindle organization (45,68). Additionally, the involvement of Mybbp1a, rpL5, and rpL11 was shown in p53 acetylation and accumulation, which is dependent on the release of Mybbp1a from nucleolar RNA upon stress (54).…”
Section: Discussionmentioning
confidence: 99%
“…Its human orthologue localizes to nucleoli in interphase and at the chromosomal periphery from prometaphase to anaphase (60). Rrs1 depletion by RNAi results in defects in chromosome congression, with mitotic cells showing aberrant chromosome alignment at the metaphase plate (60). The chromosome periphery might then act as a means of transport for various proteins, including nucleolar proteins (61).…”
Section: Discussionmentioning
confidence: 99%
“…Rrs1 is a protein required for ribosome biogenesis in yeast (59). Its human orthologue localizes to nucleoli in interphase and at the chromosomal periphery from prometaphase to anaphase (60). Rrs1 depletion by RNAi results in defects in chromosome congression, with mitotic cells showing aberrant chromosome alignment at the metaphase plate (60).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, recent research has revealed that the chromosome periphery has no relationship with chromosome condensation because condensins have been shown to play the main role in chromosome condensation as internal scaffolds (72). In fact, knockdown of a series of CPPs including histone H1.X, nucleolin, NPM and RRS1 does not influence chromosome condensation (18,30,49,60).…”
Section: Cpps Function In Chromosome Alignment Segregation and Spindmentioning
confidence: 87%
“…Knockdown of a variant of histone H1, H1.X, and a centrosomebinding protein, NPM, induces defects in kinetochoremicrotubule attachments similar to nucleolin depletion, resulting in a prolonged time from nuclear envelope breakdown to chromosome alignment (28)(29)(30)82). Depletion of a ribosome biogenesis regulatory protein, RRS1, induces the disappearance of Shugosin 1, which is responsible for centromeric protection (60). This results in premature sister chromatid separation.…”
Section: Cpps Function In Chromosome Alignment Segregation and Spindmentioning
confidence: 99%